Bidirectional regulation mechanism of TRPM2 channel: role in oxidative stress, inflammation and ischemia-reperfusion injury - Huang, Peng; Qu, Chaoyi; Rao, Zhijian; Wu, Dongzhe; Zhao, Jiexiu (Frontiers in Immunology, 2024)
Transient receptor potential melastatin 2 (TRPM2) is a non-selective cation channel that exhibits Ca 2+ permeability. The TRPM2 channel is expressed in various tissues and cells and can be activated by multiple factors, including endogenous ligands, Ca 2+ , reactive oxygen species (ROS) and temperature. This article reviews the multiple roles of the TRPM2 channel in physiological and pathological processes, particularly on oxidative stress, inflammation and ischaemia-reperfusion (I/R) injury. In oxidative stress, the excessive influx of Ca 2+ caused by the activation of the TRPM2 channel may exacerbate cellular damage. However, under specific conditions, activating the TRPM2 channel can have a protective effect on cells. In inflammation, the activation of the TRPM2 channel may not only promote inflammatory response but also inhibit inflammation by regulating ROS production and bactericidal ability of macrophages and neutrophils. In I/R, the activation of the TRPM2 channel may worsen I/R injury to various organs, including the brain, heart, kidney and liver. However, activating the TRPM2 channel may protect the myocardium from I/R injury by regulating calcium influx and phosphorylating proline-rich tyrosine kinase 2 (Pyk2). A thorough investigation of the bidirectional role and regulatory mechanism of the TRPM2 channel in these physiological and pathological processes will aid in identifying new targets and strategies for treatment of related diseases.